Plant extract with bioactive potential against SARS-CoV-2 - Melo, Adma N.F. (2022)
The novel disease caused by SARS·CoV-2 has been causing chaos worldwide due to its high mortality, morbidity and contagiousness nature, and therefore forced the scientific world to develop n'ew alternatives to combat and assist the fight against this virus. Plant extracts have bioactive molecules that might provide a starting point for the research on the use of plants as an excellent source ofoew antiviral agents able to inhibit or neutralize COVID-19. Therefore, the objective ofthis study was to obtain an extract !Tom a Plaot cultivated under controlled conditions in Portugal to be used as ao antiviral substance to be applied against COVID-19. MaterialslMethods: The plant extract obtained !Tom plant cultivated under controlled conditions in Portugal was extracted by maceration in a hydroethanolic solution under optimized conditions and submitted to freeze drying. The extracts were evaluated for their phenolic profile by high performance liquid chromatography coupled to a diode array detector and a mass spectrometer detector (HPLCDAD- MS). Antioxidant activity was also measured, and antiviral properties were measured for SARSCoV- 2 in Vero cells. Remlts. HPLC analysis revealed the presence of different phenolic compounds in the extracts with relevance for caftaric acid, cis-chicoric acid and trans-chychoric acid. The extract showed a good antioxidant capacity demonstrated by the high value found for aRAC of3202,82 ± 32,52 Troloxlmg extrac!. Regarding the antiviral activity, the results achieved for the viral titer was 20 PFU/mL, and the antiviral activity for SARS-CoV-2 was 4.02 ± 0.00 Mv and the perceotage ofreduction was > 99.99%. Conclusion: The results showed that the obtained extract demonstrated consistent results of antiviral activity presenting a potential for applications against the SARS-CoV-2. Further studies are required for validation and application of this extract.